Comprehensive Groundwater Quality Analysis in Chronic Kidney Disease of Unknown Etiology (CKDu) Prevalence Areas of Sri Lanka to Investigate the Responsible Culprit - T. D. Fernando; Yohan L. N. Mathota Arachchige; K. V. P. Sanjeewani; R. A. M. T. S. Rajaguru (Journal of Chemistry)
Chronic kidney disease of unknown etiology (CKDu) is a serious health problem in Sri Lanka especially among agricultural communities in dry zone since 19th century. In the present study, several water quality parameters were studied in well water samples and only four parameters, namely, hardness, cadmium level, fluoride level, and strontium level have shown a relationship with the CKDu prevalence. Higher percentage of well water samples collected from CKDu prevalent area in both pre and postmonsoon seasons have exceeded the WHO recommended levels of hardness. Further, water samples collected in postmonsoon seasons had significantly higher hardness than the well water samples collected in premonsoon season (P<0.05). This may be due to the dissolution of calcium carbonate by water recharge. Moreover, cadmium and fluoride contents have exceeded the recommended levels in high-risk area during the premonsoon period. Furthermore, according to principal component analysis (PCA), four clusters were identified depending on the different levels of fluoride, cadmium, hardness, and strontium contents. The control area (Am) fell in to separate cluster with low contents of fluoride, cadmium, hardness, and strontium than in CKDu prevalent area. Since it has been found that the above species are directly involved in renal damage, it can be concluded that a synergetic effect of cadmium, fluoride, hardness, and strontium in well water may be a main cause for CKDu in Sri Lanka.